Assessing Community Needs and Expectations with Healthcare Quality: A Case Study of Lawawoi Community Health Center - Muhammad Tahir; Hasrul Hasrul; Nur Annisa Parno; Asnuddin Asnuddin (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: In this study, we aimed to examine the relationship between community healthcare needs, expectations, and perceived service quality within the context of rural health service delivery. With growing global emphasis on patient centered care and rising concerns about inequitable healthcare access, our objective was to assess how well community needs and expectations align with service provision at the Lawawoi Community Health Center (CHC) to address gaps identified in existing literature. Methods: This quantitative cross sectional study involved the distribution of structured questionnaires and observational data collection conducted at the Lawawoi CHC from March to May 2024. A total of 80 respondents were enrolled through purposive sampling. Data were collected via validated surveys assessing perceptions of service quality, expectations, and healthcare needs. Ethical approval was obtained from the Institutional Review Board of the research team’s affiliated institution, and participants provided informed consent. Results: The primary outcome of the study was the perceived improvement in service quality. Findings revealed that 90.5% of participants with high healthcare needs and 94.7% of those with high expectations perceived service quality as good. Chi square tests showed statistically significant relationships between community needs and service quality (p = 0.000) and between expectations and service quality (p = 0.000). Notably, cultural values and interpersonal provider patient interactions were influential in shaping perceptions. Conclusion: In conclusion, our study contributes to the understanding of patient centered service delivery in rural Indonesia by highlighting the importance of aligning healthcare provision with community needs and expectations. This research provides insights into participatory planning, communication strategies, and culturally responsive care as drivers of perceived service quality. Future studies should explore longitudinal impacts of community engagement and evaluate continuous quality improvement models to advance equity oriented healthcare practices in resource limited settings.